Moro spaces exploring mosque architecture in Cotabato City through society, culture, history, and muslim concept of space - Makakena, Sittie Anne M. (2023)
The purpose of this study is to explore the mosque architecture in Cotabato City through the mosques? socio-cultural and historical backgrounds, their objective characteristics, their adherence to Sakili?s (2003) theory of Muslim Concept of Space, as well as the level of satisfaction of their users. The study was approached using both quantitative and qualitative methods of gathering data, analyses, and observations. The data gathering procedure involved ocular survey of 17 jami mosque structures, a total of 510 participant survey, and 16 interviews for the owners or caretakers of the mosques. To explore the extent of the theory in the data sets, the principles under the Muslim Concept of Space were also provided with definition, measures, and indicators. By ranking the mosques according to their level of adherence to the principles, the level of adherence was identified and set. Meanwhile, Level of Satisfaction of the users were determined using Likert scale implemented in the participant survey questionnaires. Through this, it was concluded that the Muslim people of Cotabato City are generally either satisfied or very satisfied with their community mosques. The data in both adherence to Muslim Concept of Space and the Satisfaction of the users were used to find correlation among their variables.As Spearman?s Order-Ranking Correlational Analysis was implemented to analyze the data, it was found that there is an inverse correlation between the theory and the satisfaction of the users which means that as the level of adherence to the theory increases, the level of satisfaction of the users decreases. On the other hand, the background study of the mosques has revealed that their funding and construction are either foreign, local, or both foreign and local funded. Majority are also self-sustained through donations and are not supported by the government. Incremental building is also apparent in some of the sample buildings as resources and donations are often scarce or delayed. The research has also documented each of the study areas through pictures and drawings which are helpful in establishing guidelines or interventions in mosque architecture. Future planners and researchers may use these results for further study and exploration of Islamic architecture in the Philippines.